ABO, Lewis, secretor and non-secretor phenotypes in patients infected or uninfected by the Helicobacter pylori bacillus - De Mattos, Luiz Carlos; Cintra, Juliana Rodrigues; Sanches, Fábio Eduardo; Alves Da Silva, Rta de Cássia Martins; Ruiz, Milton Artur; Moreira, Haroldo Wilson [UNESP] (FapUNIFESP (SciELO), 2002)
CONTEXT: Epidemiological studies have demonstrated higher frequencies of the O blood group and the non-secretor phenotype of ABH antigens among patients suffering from peptic ulcers. Since Helicobacter pylori has been established as the main etiological factor in this disease, controversies about the associations of the ABO and Lewis blood group phenotypes and secretor and non-secretor phenotypes in relation to susceptibility towards infection by this bacillus have been presented. OBJECTIVE: To verify the frequencies of ABO, Lewis blood group phenotypes, secretor and non-secretor phenotypes in patients infected or uninfected by H. pylori. DESIGN: Cross-sectional study. SETTING: Outpatient clinic. PARTICIPANTS: One hundred and twenty patients with dyspeptic symptoms who underwent endoscopy. MAIN MEASUREMENTS: ABO and Lewis blood group phenotypes were determined by a standard hemagglutination test and the secretor and non-secretor phenotypes were evaluated by saliva samples using the inhibitor hemagglutination test. RESULTS: The diagnosis of infection, made via breath and urea tests and confirmed using polymerase chain reaction (PCR) in gastric biopsy fragments, showed the presence of H. pylori in 61.7% of the patients and absence in 38.3%. The differences between the frequencies of the ABO blood group phenotypes among infected (A 27.0%; B 12.2%; AB 4.0% and O 56.8%) and uninfected patients (A 58.7%; B 13.0%; AB 4.3% and O 24.0%) were significant. The Lewis blood type, secretor and non-secretor phenotypes showed homogeneous distribution between the groups of patients analyzed. CONCLUSIONS: Our results suggest that the infection of H. pylori can be related to ABO blood groups but not to the Lewis blood group nor to secretor and non-secretor phenotypes. Copyright©2002, Associação Paulista de Medicina.
Keywords: ABO; Blood groups; Helicobacter pylori; Lewis; Non-secretor phenotype; Secretor phenotype; bacterial infection; blood group ABO system; blood group Lewis system; controlled study; dyspepsia; endoscopy; hemagglutination test; human; major clinical study; outpatient department; phenotype; polymerase chain reaction; saliva; stomach biopsy; urea breath test; adolescent; adult; aged; blood; cross-sectional study; female; Helicobacter infection; male; microbiology; ABO Blood-Group System; Adolescent; Adult; Aged; Cross-Sectional Studies; Dyspepsia; Female; Helicobacter Infections; Hemagglutination Tests; Humans; Lewis Blood-Group System; Male; Phenotype; Polymerase Chain Reaction